EVALUATING THE EARLY OUTCOMES OF USING POLYMERIC MESHES IN SURGICAL MANAGEMENT OF PELVIC FLOOR PROLAPSE AT THE OBSTESTRICS DEPARTMENT OF NGHE AN GENERAL FRIENDSHIP HOSPITAL (Vietnam Journal of Community Medicine, 2022)
Objectives: To evaluate the effectiveness and safety of polypropylene mesh in the surgicalreconstruction of pelvic floor in patients with pelvic organ prolapse (POP) at Nghe An FriendshipGeneral Hospital.Subjects and Methods: Case reports of female patients with pelvic organ prolapse treated atNghe An General Friendship Hospital who assigned for surgery to reconstruct the pelvic floor withpolymeric mesh.Results: Between June 2020 to June 2021, among 48 selected patients underwent surgery, theaverage age was 61.3 years, the proportion of patients who were in pregnant equal to or greaterthan 3 times was 83.3%; The proportion of bladder prolapse, uterine prolapse and rectus prolapsewere 89.5%, 83.3% and 31.2%, respectively. Laparoscopic surgery accounted for 72.8% of totalcases and sacrocolpopexy accounted for 28.2%. The average time of sacrocolpopexy was 130 ± 39minutes with the blood loss of 160±37 ml. The average time of mesh placement for reconstructionof the anterior wall of the vagina was 61±6 minutes, the average blood loss was 56 ± 13 ml. Sacralpain occurred in 3 out of 48 patients. Overactive bladder was seen in 3 out of 48 patients.Conclusions: The placement of polymeric mesh to repair the pelvic organ prolapse can beperfomed transvaginal or laparoscopy surgery. In our study, there was no recurrence duringfollow-up. The rate of early and long term complications was low. The quality of life of patientswas improved after surgery.
Keywords: Pelvic organ prolapse, laparoscopic, sacrocolpopexy.